2015
DOI: 10.1074/jbc.m115.636316
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Activation of a G Protein-coupled Receptor with Cell-penetrating Receptor Mimetics

Abstract: Background: Intracellular parts of GPCRs have yet to be effectively exploited as allosteric modulators. Results: The structure and mechanism of action of a lipidated pepducin agonist is determined. Conclusion:The pepducin requires the H8 helix and TM7 tyrosine propeller to stabilize the on-state and trigger receptor-G protein signaling. Significance: This work provides critical insight into the identification of allosteric modulators to this major drug target class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 66 publications
2
27
0
Order By: Relevance
“…Through this approach, selective PAR1 and PAR2 agonist and antagonist pepducins have been generated [46]. Recent interrogation of the binding properties of the ICL3 PAR1 agonist pepducin, P1pal-19 revealed direct interaction with helix 8 (H8) of PAR1 [47]. In this study, activation of PAR1 by P1pal-19 involved the (D/N)PXXY motif in transmembrane-7 (TM7) and direct engagement with H8.…”
Section: Non-competitive Modulators Of Par Activitymentioning
confidence: 91%
“…Through this approach, selective PAR1 and PAR2 agonist and antagonist pepducins have been generated [46]. Recent interrogation of the binding properties of the ICL3 PAR1 agonist pepducin, P1pal-19 revealed direct interaction with helix 8 (H8) of PAR1 [47]. In this study, activation of PAR1 by P1pal-19 involved the (D/N)PXXY motif in transmembrane-7 (TM7) and direct engagement with H8.…”
Section: Non-competitive Modulators Of Par Activitymentioning
confidence: 91%
“…For ICL3-9, a Cys 265 -monobromobimane-conjugated β 2 AR showed that the pepducin does not operate through conventional receptor activation and uniquely couples G s to the receptor [5]. In assessing the mechanism of P1pal-19's ability to activate PAR1 signalling, Zhang et al [35] used a Cys 296 -monobromobimane-conjugated PAR1 to demonstrate that P1pal-19 was able to stabilize a conformation of PAR1 that may be similar to the cognate endogenous agonist, thrombin. Further, through mutagenesis studies, the authors were able to identify critical regions in PAR1 for pepducin interaction (helix 8) and efficacy ((D/N)PXXYYY motif in transmembrane 7).…”
Section: New Insight Into the Mechanism Of Actionmentioning
confidence: 98%
“…The identification of the first allosteric GPCR modulators was empirical, decades before the receptor structures were elucidated, and in some cases we now understand their structural basis. Five X-ray structures of GPCR allosteric complexes can be compared (Figure 7): muscarinic acetylcholine (Family A), corticotropin releasing hormone 1 (CRF 1 , Family B), mGlu 1 (Family C), P2Y 1 receptors (Family A) and GPR40 [92,96], with bound allosteric modulators, LY2119620 (PAM) 48 , CP-376395 (NAM) 49 , FITM (NAM) 50 , BPTU (NAM) 51 and TAK-875 (PAM, allosteric partial agonist) 52 , respectively. In each case, the location, relative to the orthosteric site is different.…”
Section: New Pharmacological Dimensionsmentioning
confidence: 99%